2012
DOI: 10.1074/mcp.m111.010884
|View full text |Cite
|
Sign up to set email alerts
|

In-depth Identification of Pathways Related to Cisplatin-induced Hepatotoxicity through an Integrative Method Based on an Informatics-assisted Label-free Protein Quantitation and Microarray Gene Expression Approach

Abstract: Cisplatin is used widely for treatment of a variety of cancer diseases. Recently, however, the use of cisplatin is restricted because of its adverse effects such as hepatotoxicity. There is no study with current proteomics technology to evaluate cisplatin-induced hepatotoxicity, even if some studies have reported on the hepatotoxicity. In this study, proteomic as well as genomic analyses have been used for identification of proteins and genes that respond to cisplatin treatment in rat primary hepatocytes. To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 77 publications
1
69
0
Order By: Relevance
“…Quantitative proteomics analysis reveals that PDIA3, DJ-1, and GSTO had significantly changed expression in the HeLa/CDDP-resistant group (61). Notably, these proteins also significant changed under CDDP inducement in rat primary hepatocytes (62), and in our study, they are considered as potential TEA biomarkers. It might be concluded that TEA induced HeLa apoptosis not only by blocking KChs but also by following previous and credible the mechanism, such as CDDP, initiating a similar or the same apoptotic biological pathway.…”
Section: Tea Inhibits Hela Cell Proliferation and Induces Cellmentioning
confidence: 80%
See 1 more Smart Citation
“…Quantitative proteomics analysis reveals that PDIA3, DJ-1, and GSTO had significantly changed expression in the HeLa/CDDP-resistant group (61). Notably, these proteins also significant changed under CDDP inducement in rat primary hepatocytes (62), and in our study, they are considered as potential TEA biomarkers. It might be concluded that TEA induced HeLa apoptosis not only by blocking KChs but also by following previous and credible the mechanism, such as CDDP, initiating a similar or the same apoptotic biological pathway.…”
Section: Tea Inhibits Hela Cell Proliferation and Induces Cellmentioning
confidence: 80%
“…In addition, DJ-1, PDIA3, and GSTO were selected as differential proteins in TEA-treated groups; they are also regulated proteins in CDDPresistant HeLa cells studies (61) as well as in a rat primary hepatocyte study of CDDP toxicity (62), and some important differential proteins are discovered in the p53-dependent apoptosis pathway as described above. These results provide new details on the new molecular pathway involved in apoptosis and give a broader context of apoptotic events in therapeutic strategies.…”
Section: Tea Inhibits Hela Cell Proliferation and Induces Cellmentioning
confidence: 99%
“…Cisplatin is becoming increasingly a favor to clinical doctors attributed to its unique clinical benefit. Unfortunately, cisplatin therapy brings about undesirable side effects, including renal dysfunction 4 , ototoxicity 5 , nausea and vomiting 6 , and hepatotoxicity 7 . Hepatotoxicity is not considered to be a dose limiting toxicity for cisplatin, but liver toxicity can occur when it is administered at high doses 8 , which has been an obstacle for the further usage of cisplatin.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several studies have already demonstrated the usefulness of using specific DNA or RNA sequences in the circulation, such as transcripts highly enriched in the liver, as markers to reflect DILI. 11,67,91 The concentrations of these molecules are too low to conduct a global survey using traditional nucleic acid profiling approaches like microarray. Besides microRNA, due to its small repertoire, no systematic survey of the DNA or RNA spectrum in the circulation has been done.…”
Section: Approaches For New Biomarker Discoverymentioning
confidence: 99%